Adaptation for Mitigation - Masako Ikefuji; Jan R. Magnus; Hiroaki Sakamoto (Fondazione Eni Enrico Mattei (FEEM), 2014)
This paper develops a dynamic model consisting of two regions (North and South), in which the accumulation of human capital is negatively influenced by the global stock of pollution. By characterizing the equilibrium strategy of each region, we show that the regions best responses can be strategic complements through a dynamic complementarity effect. The model is used to analyze the impact of adaptation assistance from North to South. It is shown that Norths unilateral assistance to South (thus enhancing Souths adaptation capacity) can facilitate pollution mitigation in both regions, especially when the assistance is targeted at human capital protection.
Keywords: D91; Q54; Q58; 330; Climate Change; Mitigation; Adaptation; Human Capital